Forceps minor control of social behaviour - Franziska Stoller; Eleanor Hinds; Tudor Ionescu; Elmira Khatamsaz; Hugh M. Marston; Bastian Hengerer (Scientific Reports)
Abstract The PRISM project, funded by the EU’s Innovative Medicines Initiative, has identified a transdiagnostic, pathophysiological relationship between the integrity of the default mode network (DMN) and social dysfunction. To explore the causal link between DMN integrity and social behaviour, we employed a preclinical back-translation approach, using focal demyelination of the forceps minor to disrupt DMN connectivity in mice. By applying advanced techniques such as functional ultrasound imaging and automated analysis of social behaviour, we demonstrated that reduced DMN connectivity leads to impaired social interactions and increased anxiety in mice. Notably, these effects were reversible, indicating that the forceps minor, a critical fibre tract connecting key DMN regions in the prefrontal cortex, plays a crucial role in social function. This study provides direct evidence for a causal relationship between DMN integrity and social dysfunction, with potential implications for developing targeted treatments in precision psychiatry.